Kesalehan dan Ketekunan Ayub Kepada Allah dalam Penderitaan-Nya - Yohanes Yappo; Callista Anugrahni; Tirza Tanzania; Sarmauli Sarmauli (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
The purpose of writing this article is to identify and know the life story of the character of Job. The character of Job is a person who has a righteous personality, is honest, fears God, and shuns evil. The story begins with a portrayal of a man who is very pious, blessed and wealthy, then continues with a severe test that changes his life.